RARE-19. PEDIATRIC HIGH GRADE GLIOMA WITH DNA REPAIR PATHWAY ABERRATIONS, CLINICAL CHARACTERISTICS AND OUTCOME. (4th December 2020) - Baig, Muhammad; McCall, David; Moss, Tyler; Sandberg, David; Fuller, Gregory; McGovern, Susan; Paulino, Arnold; Najjar, Amer; Chandra, Joya; Khatua, Soumen; Zaky, Wafik
Abstract: DNA mismatch repair machinery is an integral part of the human genome and its defect has been involved in tumorigenesis and treatment resistance. Heterozygous monoallelic germline loss of function in MLH-1, MSH-2, MSH-6 or PMS-2 is involved in Lynch syndrome, whereas biallelic mutations cause constitutional mismatch repair deficiency (CMMRD) which is associated with hematologic malignancies and glioblastoma. We report here the clinical characterization and molecular analyses of 7 patients who presented with gliomas and MMR machinery aberrations. Two patients had a clinical diagnosis of NF-1 with dermatologic stigmata, of whom one patient has CMMRD and the other has Lynch syndrome. Two patients had a known family history of Lynch syndrome upon their diagnosis of glioma. Three patients with high-grade glioma and negative family history, 2 had germline mutations in MMR genes, and one had numerous mutations including MMR genes with microsatellite instability. Patients were initially treated with chemotherapy and radiation for high-grade gliomas (HGG); 5/7 had progression. Median time to progression was 12 months (range: 5–52), and median time from progression to death was 7 months (range: 2–25). One patient had low-grade glioma initially but progressed to HGG and is currently on therapy. Another patient treated with temozolomide and radiation is currently receiving maintenance therapy without any disease recurrence. Although the literature data on brain tumors with MMR deficiency is limited, these consistently show that MMRD-associated gliomas are treatment-resistant and have a dismal outcome. Collaborative efforts are needed to better understand this subgroup of pediatric HGG and to define optimal treatment strategy.